Implementation of Religious Moderation in Muslim Families Bagan Siapiapi, Riau in the Perspective of Fath al-Dzarī’ah - Arisman, Arisman; Harmanto, Adi; Sobirin, Imam (Universitas Islam Negeri Raden Intan Lampung, 2023)
This article aims to describe the concrete efforts made by Muslim families in Bagansiapiapi, Riau in implementing the concept of religious moderation to create a harmonious atmosphere in the midst of a pluralistic society. This research is a field research, with a sociological-empirical approach. Data collection techniques are carried out by observation, interviews and documentation. The research informants consist of ten Muslim families in Bagan Siapiapi as key informants. The data that have been collected are then processed to be analyzed qualitatively-descriptively-analystically through the fath al-dzarī’ah theory. The results of this study indicate that there are four efforts of religious moderation that have been implemented by the Bagan Siapiapi community, namely: first, the